ANSWER
The substitution property of equality.
EXPLANATION
We know that:
![12x = 60](https://tex.z-dn.net/?f=12x%20%3D%2060)
and that
![x = 5](https://tex.z-dn.net/?f=x%20%3D%205)
Since x=5 or 5=x , we can substitute x for 5 wherever we see x in the given equation.
When we do that, we obtain;
![12 \bullet \: 5 = 60](https://tex.z-dn.net/?f=12%20%5Cbullet%20%5C%3A%205%20%3D%2060)
This is what we refer to as the substitution property of equality.
First subtract the x variable on both sides so on the first equation youll have -6y=8x+60 then divide 6 on all variables which means youll have y=8/6x+10 and in the second equation you do the same thing and youll have y=-5/6x-11.5
Very easy:
Common denominator:
-5/10w - 3/5 = 2/10w
- 3/5 = 7/10w
-30 = 35w
-30/35 = w
-6/7 = w
That's how you do it mate ;)
Answer:
Eight times ten plus six times one plus two times one-tenth plus seven times one-thousandth.
Step-by-step explanation:
(8 x 10) = eight times ten
(6 x 1) = six times one
(2 x 0.1) = two times one-tenth
(7 x 0.001) = seven times one-thousandth
I am not always the best with the equations to words stuff, so please comment if I am wrong!